“Traditional Natural Law as the Source of Western Constitutional Law, Particularly in the United States”: Dante Figueroa - Anaut, Manuel (Derecho Público Iberoamericano, 2020)
Dante Figueroa, "Traditional Natural Law as the Source of Western Constitutional Law, Particularly in the United States", Panamá, Editorial Jurídica Venezolana Internacional, 2014, 164 págs.